Grid power quality enhancement by nonlinear control of voltage source inverter - Muhammad imran; zhang jianmeng; abdullah naveed; mohammad ahsan shehzad; cui guoqiang (Journal of Engineering Research and Reviews)
Aim/Background: Maintaining power quality in grid-connected systems with renewable energy sources, particularly solar, is a significant challenge due to stringent requirements for harmonic mitigation. Voltage source inverters serve as critical interfaces between the grid and renewable energy sources but require robust control strategies to ensure power quality.